2012
DOI: 10.1021/ct300559t
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Expansions of Orbitals

Abstract: Using numerical calculations and analytic theory, we examine the convergence behavior of Gaussian expansions of several model orbitals. By following the approach of Kutzelnigg, we find that the errors in the energies of the optimal n-term even-tempered Gaussian expansions of s-type, p-type, and d-type exponential orbitals are ε n s ∼ exp(−π(3n) 1/2 ), ε n p ∼ exp(−π(5n) 1/2 ), and ε n d ∼ exp(−π(7n) 1/2 ), respectively. We show that such "root-exponential" convergence patterns are a consequence of the orbital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Studies [69,70] suggest that while the FD approach for transition dipoles shows improved convergence behavior compared to the EV approach, perhaps more so than for Spherically averaged polarizability of water in its equilibrium geometry computed using sum-over-states formula (1) [73]; the experimental value is corrected for vibrational effects [75].…”
Section: Electron Correlation Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [69,70] suggest that while the FD approach for transition dipoles shows improved convergence behavior compared to the EV approach, perhaps more so than for Spherically averaged polarizability of water in its equilibrium geometry computed using sum-over-states formula (1) [73]; the experimental value is corrected for vibrational effects [75].…”
Section: Electron Correlation Treatmentmentioning
confidence: 99%
“…the diagonal dipole moments, there are technical issues with their use that still need to be overcome [70,71].…”
Section: Electron Correlation Treatmentmentioning
confidence: 99%
“…Klopper and Kutzelnigg109–111 showed that the energy of a hydrogen atom converges exponentially with the square‐root of the number of Gaussian functions used for expanding the 1s‐orbital, as shown in Eq. (12): …”
Section: Basis Set Convergence Of Independent‐ and Correlated‐electromentioning
confidence: 99%
“…Given that the fitting errors (Table III) in the gLDA1 functional can be of the order of 0.1 mE h , we aimed to obtain the energies of the n-boxium and n-hookium to within 0.1 mE h of their complete basis set (CBS) limits. This is easily achieved for the HF, LDA1 and gLDA1 energies, because they converge exponentially [90][91][92] with the size M of the one-electron basis, but it is less straightforward for traditional post-HF energies.…”
Section: The Lda1 Glda1 and Glda1 Functionalsmentioning
confidence: 99%